2022
DOI: 10.1097/pr9.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Task-specific fear rather than general kinesiophobia assessment is associated with kinematic differences in chronic low back pain during lumbar flexion: a preliminary investigation

Abstract: Clinicians should consider the potential added value of task-specific fear assessment over the sole use of general kinesiophobia assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…52 This may not be due to slowed movement so much as alternative joint coordination choices 86 and stops and hesitation in movement 94 (associated with fear of movement 39,67,71 ). The relationship between fear and movement detection seems stronger when the fear of movement is measured in relation to the movement task 26,27,38 rather than the total TSK score 38,54 or pain-related anxiety 85 rather than general anxiety. 46,90…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…52 This may not be due to slowed movement so much as alternative joint coordination choices 86 and stops and hesitation in movement 94 (associated with fear of movement 39,67,71 ). The relationship between fear and movement detection seems stronger when the fear of movement is measured in relation to the movement task 26,27,38 rather than the total TSK score 38,54 or pain-related anxiety 85 rather than general anxiety. 46,90…”
Section: Resultsmentioning
confidence: 97%
“…1,3,88 Task-specific fear might be expected to be more closely related to performance than broader fear of movement. 38 In addition, there is some evidence that movement velocity captures kinematic features affected by fear of movement better than do displacement and ROM measures, 39,64,72,86 with longer time of movement execution associated with fear of movement. 70,72 A recent virtual reality study using both headset and handheld sensors found changes in movement velocity to be associated with both fear of movement and reinjury and chronic low back pain.…”
Section: Movement and Activity Monitorsmentioning
confidence: 99%
“…Because the arousal of fear in general daily life and fear about specific movements differ, the results of each assessment are not correlated. 49 An earlier study showed that task-specific fear, rather than generalized fear of movement, is useful in predicting motor behavior. 49 In this study, the TSK and the NRS were completed by the LBP subject, and his NRS score decreased more immediately in the intervention phase.…”
Section: Discussionmentioning
confidence: 99%
“… 49 An earlier study showed that task-specific fear, rather than generalized fear of movement, is useful in predicting motor behavior. 49 In this study, the TSK and the NRS were completed by the LBP subject, and his NRS score decreased more immediately in the intervention phase. Therefore, among aspects of fear of movement, the improvement of task-specific fear might have contributed to the improvement of impaired trunk movement in the LBP subject.…”
Section: Discussionmentioning
confidence: 99%
“…The Tampa Scale of Kinesiophobia (TSK) measures “fear of movement” or “kinesiophobia” in the patient [ 21 ]. The total score on this scale is from 17 to 68 [ 22 ].…”
Section: Methodsmentioning
confidence: 99%